Microbiological and Immunological Investigation of adult patients with Chronic Sinusitis - Jreemich, Samira Kgeer (University of Thi-Qar Journal, 2019)
The present study was conducted in Al-Diwaniya Teaching Hospital ENT department at the period from November 2013 to March 2014 One hundred adult patients clinically presented with chronic sinusitis were selected for this study , swabs were taken from middle meatus by special designed swab under endoscopic guidance from both patients and controls(50 healthy individuals)to identify the causative microorganisms of sinusitis. It was found that from 100 patients, only 10% have no growth while 90% yielded growth of various microorganisms of which the most common pathogens were Staphylococcus aureus , Streptococcus pneumoniae ,Haemophilus influenzae and Moraxella catarrhalis. The immunological investigations (IgG, IgM, IgA, C3 & C4) revealed that 99 patients were immune competent while (3) patients showed some immune defect .